2020
DOI: 10.1111/cpr.12960
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal squamous cell carcinoma–associated IL‐33 rewires macrophage polarization towards M2 via activating ornithine decarboxylase

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…M2 macrophages produce urea, polyamines, and ornithine through ARG1, which are essential for the function of macrophages in wound healing [115]. Ornithine secreted by M2 macrophages promotes tumor growth and metastasis by activating tumor cell IL-33 expression [116]. Glucose metabolism promotes tumor progression by inhibiting cell death and exerts antiinflammatory effects in ischemic gut mucosa.…”
Section: Metabolic Alterations Of Tams In Crcmentioning
confidence: 99%
“…M2 macrophages produce urea, polyamines, and ornithine through ARG1, which are essential for the function of macrophages in wound healing [115]. Ornithine secreted by M2 macrophages promotes tumor growth and metastasis by activating tumor cell IL-33 expression [116]. Glucose metabolism promotes tumor progression by inhibiting cell death and exerts antiinflammatory effects in ischemic gut mucosa.…”
Section: Metabolic Alterations Of Tams In Crcmentioning
confidence: 99%
“…Protein extraction reagent (Beyotime) and BCA protein quantification reagent (Abcam, Cambridge, UK) were used for protein extraction and quantification respectively. WB was executed according to a previous report [ 29 ]. The extracted protein samples were separated using SDS-PAGE (Beyotime), followed by transferring to nitrocellulose membranes (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…A study reported that peroxisome proliferator-activated receptor gamma (PPARγ) is involved in the interaction between IL-33 and group 2 innate lymphoid cells (ILC2) ( 49 ). By activating ornithine decarboxylase, which catalyses the synthesis of polyamines, IL-33 induces M2-like macrophage polarization ( 50 ). IL-33 is also able to induce the gene expression of Th2-associated cytokines such as IL-5 and IL-13 ( 34 ).…”
Section: An Overview Of Il-33mentioning
confidence: 99%